PENGARUH AHH, IDG, DAN JP TERHADAP IPM DI INDONESIA - Siti Khairani Simanjuntak; Devi Andriyani (JURNAL EKONOMIKA INDONESIA, 2021)
This study examined the influence of the Life Expectancy Rate, Gender Empowerment Index, and Population Number on the Human Development Index in Indonesia. This study used panel data with time- series data for 6 years from 2015 to 2020 and cross-section data for 5 provinces in Indonesia obtained from the Central Bureau of Statistics. The method of data analysis used was the Random Effect Model using Eviews 10. The results indicated that the life expectancy rate positively and significantly influenced the human development index, the gender empowerment index positively but insignificantly influenced the human development index, and the population negatively and insignificantly influenced the human development index. The researcher hopes that the government can improve the quality of human resources in the fields of health and education so that later the community can compete with other provincesKeywords:Human Development Index, Life Expectancy, Gender Empowerment Index, and Population